Human Resource Development Strategy Based on Learning Psychology: A Case Study at PT. TB Global Group - Puteri, Andrea; Syukur, Aris Muhamad; Cedaryana, C. (Manunggal Halim Jaya, 2025)
This research is motivated by the importance of psychological understanding in human resource (HR) development in the modern workplace. This study aims to address the question: How are the principles of learning psychology applied in HR development at PT TB Global Group, and how do they affect team member motivation, engagement, and performance? A qualitative approach with a case study method was employed. Data were obtained through observations of training and team member development processes and analysis of internal documentation. The principles of learning psychology, which include behaviorism, cognitivism, constructivism, and humanism, were applied in training programs, coaching, and career development. The findings reveal that this approach successfully enhances employee engagement and motivation. Most employees feel more valued, have room to grow, and are more actively contributing within teams. The work environment has also become more supportive, collaborative, and oriented toward continuous learning. These findings indicate that a holistic and contextual psychological approach can promote improved performance and strengthen commitment to the company.